The Effectiveness of Project-Based Learning in Chemistry Learning: Conceptual Understanding and 21st Century Skills - Aura, Aura Nawang Wulan; Matius, Dewi; Riani, Khotijah Mahmuda Widi; Dakhi, Yofita Jelita Linda Sari; Fad’ah, Akhmad Syaikah Nur; Wirhanuddin, Wirhanuddin (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Project-Based Learning (PjBL) is a student-centered learning model considered effective in improving conceptual understanding and developing 21st-century skills in chemistry learning. This study aims to systematically assess the effectiveness of PjBL implementation on students’ conceptual understanding, learning outcomes, and 21st-century skills in chemistry learning. This study used the Systematic Literature Review (SLR) method, referring to the PRISMA steps, which include article identification, screening, eligibility assessment, and inclusion. Literature sources were obtained from Google Scholar and Scopus databases based on established inclusion and exclusion criteria. Of the 824,157 articles identified, 20 articles published between 2022 and 2026 met the criteria and were further analyzed. The results showed that most studies reported positive impacts of PjBL on improving students’ conceptual understanding, learning outcomes, critical thinking skills, creativity, communication, and collaboration. Furthermore, project-based activities make the chemistry learning process more contextual, meaningful, and relevant to everyday life. Despite this, several obstacles were still encountered, such as limited learning time, inadequate facilities and infrastructure, varying teacher preparedness, and imbalanced student participation in group work. The findings and percentages presented in this study are a synthesis of the reviewed articles and not derived from direct experimental data. This study also has limitations in the form of differences in research design, learning context, and variations in Project-Based Learning (PjBL) implementation in each analyzed study. Overall, the study results indicate that Project-Based Learning (PjBL) has the potential to be an effective learning approach to improve conceptual understanding, learning outcomes, and 21st-century skills in chemistry education when implemented optimally.